2014
DOI: 10.1063/1.4879899
|View full text |Cite
|
Sign up to set email alerts
|

Physics of the multi-functionality of lanthanum ferrite ceramics

Abstract: In the present work, we have illustrated the physics of the multifunctional characteristics of nano-crystalline LaFeO3 powder prepared using auto-combustion synthesis. The synthesized powders were phase pure and crystallized into centro-symmetric Pnma space group. The temperature dependence of dielectric constant of pure LaFeO3 exhibits dielectric maxima similar to that observed in ferroelectric ceramics with non-centrosymmetric point group. The dielectric relaxation of LaFeO3 correlates well with small polaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 31 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Similarly, the typical composition of REFe 0.5 Cr 0.5 O 3 (RE=La, Tb, Ho, Er, Yb, Lu and Y) was prepared by Hydrothermal method [21]. Numerous literatures are available for preparing LaFeO 3 nano powder by sol gel combustion methods [22][23][24]. But, we found that the LaFe 1-x Cr x O 3 nanopowder solid solution M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 prepared by citrate method was hard to find in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the typical composition of REFe 0.5 Cr 0.5 O 3 (RE=La, Tb, Ho, Er, Yb, Lu and Y) was prepared by Hydrothermal method [21]. Numerous literatures are available for preparing LaFeO 3 nano powder by sol gel combustion methods [22][23][24]. But, we found that the LaFe 1-x Cr x O 3 nanopowder solid solution M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 prepared by citrate method was hard to find in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…We have already reported that for unmodified LaFeO 3 , the dielectric dispersion in a wide temperature range is very well correlated to hole polaron conduction both in bulk grain and grain boundary regions [18]. Also the nature of the temperature dependence of dielectric constant is similar to conventional ferroelectric ceramics; however, for centro-symmetric point group (Pnma) dipolar polarization is not expected.…”
Section: Effect Of A-site Pb 2+ Dopantmentioning
confidence: 91%
“…The details of the powder synthesis have been reported in our earlier publication [18]. To prepare La 1Àx Pb x FeO 3 (0 6 x 6 0.2) sol, stoichiometric precursor salts (lanthanum, lead and iron nitrate) are first dissolved in distilled water through continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations